2017
DOI: 10.1016/j.gca.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear hydroxyl radical formation rate in dispersions containing mixtures of pyrite and chalcopyrite particles

Abstract: The formation of hydroxyl radicals was studied in mixed pyrite-chalcopyrite dispersions in water using the conversion rate of adenine as a proxy for hydroxyl radical formation rate. Experiments were conducted as a function of pH, presence of phosphate buffer, surface loading, and pyrite-to-chalcopyrite ratio. The results indicate that hydroxyl radical formation rate in mixed systems is non-linear with respect to the rates in the pure endmember dispersions. The only exception is a set of experiments in which ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…On the other hand, this heterogeneous catalyst can be further reutilized. According to previous research, persistent organic pollutants (i.e., sulfamethazine, trichloroethylene, and 1,4-dioxane) can be degraded by hydroxyl radicals produced during Fenton reactions. ,, …”
Section: Characteristics and Application Of Pyrite In Wastewater Trea...mentioning
confidence: 99%
“…On the other hand, this heterogeneous catalyst can be further reutilized. According to previous research, persistent organic pollutants (i.e., sulfamethazine, trichloroethylene, and 1,4-dioxane) can be degraded by hydroxyl radicals produced during Fenton reactions. ,, …”
Section: Characteristics and Application Of Pyrite In Wastewater Trea...mentioning
confidence: 99%
“…Ke et al [9] demonstrated that there is a galvanic interaction between the grinding media and the sulfide minerals because of the semiconducting nature of the sulfide minerals. During grinding, electrons will be transferred from the active material with a lower rest potential to the noble material with a higher rest potential [10]. The rest potential of common iron-based grinding media is generally lower than that of common sulfide minerals (pyrite, chalcopyrite, galena, and sphalerite, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In natural environments, microorganisms are commonly exposed to oxidative stresses ( Cooper et al, 1988 ; Mopper and Zhou, 1990 ; Hakkinen et al, 2004 ; Kaur and Schoonen, 2017 ) in which a variety of substances (e.g., pyrite, manganese oxides, and pyrithione) spontaneously react with molecular oxygen to produce H 2 O 2 ( Borda et al, 2001 ; Schoonen et al, 2010 ; Kong et al, 2015 ), especially with the mediation of light ( Mopper and Zhou, 1990 ; Zuo and Deng, 1999 ) and organic substances ( Zuo and Hoigne, 1993 ). In this study, the effects of H 2 O 2 and Mn 2+ ion on growth, Mn 2+ acquisition, anti-oxidative system and biofilm formation by P. putida MnB1 were assayed.…”
Section: Introductionmentioning
confidence: 99%